A numerical study of the locally unstable barotropic easterly jet - TUPAZ, J. B.; WILLIAMS , R.T.; CHANG, C.P. (MAUSAM, 1978)
The structure and behaviour of barotropically unstable disturbances in the vicinity of the upper tropospheric easterly jet during the summer monsoon is studied numerically with a linearized barotropic vorticity equation on an equatorial Beta-plane. The easterly jet is approximated by a Bickley jet with a slow zonal variation, and the numerical results are compared with those of a simple theoretical model using the local phase speed and growth rate concepts. In the unstable region the resultant structure of the waves causes a spatial growth greater than that predicted by the local growth rates deduced from a parallel flow model. In the stable region the structure leads to strong dynamic damping. The implications of the removal of planetary scale kinetic energy by the unstable short waves are also discussed.